Comparative Analysis for The Multi Period Degree Minimum Spanning Tree Problem - . Wamiliana; . Amanto; Mustofa Usman (International Conference on Engineering and Technology Development (ICETD), 2013)
The Multi Period Degree Constrained Minimum Spanning Tree Problem (MPDCMST) concerns of finding the total minimum cost of networks installation, where the installation process is divided into some periods. In the beginning of installation process, thecenter of the networks already set (as server, reservoir, etc). The installation process is divided into some period due to some factors, usually fund limitation. During the installation process, the networks is supposed to be maintained its reliability by restrict the numbers of links that can be connected to the node that already in the networks. In this paper we will discuss and improve the performance of WADR1 and WADR2 algorithms by setting the number of elements in the set of vertices that must be in installed in a certain period as a fix number and adding the length of the path in DFS. The result shows that the modifications works better.